Formalizing the software development process - Pons, Claudia (2001)
Object-oriented software development process, such as the Unified Process [Jacobson 99], Catalysis [D´Souza 98] and Fusion [Coleman 94] among others, is a set of activities needed to transform user’s requirements into a software system. A software development process typically consists of a set of software development artifacts together with a graph of tasks and activities. Software artifacts are the products resulting from software development, for example, a use case model, a class model or source code. Tasks are small behavioral units that usually results in a software artifact. Examples of tasks are construction of a use case model, construction of a class model and writing code. Activities (or workflows) are units that are larger than a task. Activities generally include several tasks and software artifacts. Examples of activities are requirements, analysis, design and implementation. Modern software development processes are iterative and incremental, they repeat over a series of iterations making up the life cycle of a system. Each iteration takes place over time and it consists of one pass through the requirements, analysis, design, implementation and test activities, building a number of different artifacts. All these artifacts are not independent. They are related to each other, they are semantically overlapping and together represent the system as a whole. Elements in one artifact have trace dependencies to other artifacts. For instance, a use case (in the use-case model) can be traced to a collaboration (in the design model) representing its realization.